Assessment of Neck Grasp as a Screening Tool for Identifying Obstructive Sleep Apnea in Community-Dwelling Older Adults - Oscar H. Del Brutto; Robertino M. Mera; Bettsy Y. Recalde; Pablo R. Castillo (SAGE Publishing, 2020)
Background Inability to encircle the neck by hands (neck grasp) has been proposed as an indicator of obstructive sleep apnea (OSA) that would be useful for recognition of candidates for polysomnography (PSG). We assessed the value of neck grasp for predicting OSA in community-dwelling older adults of Amerindian ancestry. Methods Neck grasp was evaluated in individuals aged ≥60 years undergoing PSG. The association between neck grasp and OSA was assessed by logistic regression models adjusted for relevant covariates. Mediation analysis was used to establish the proportion of the effect of the association between neck grasp and OSA, which is mediated by the neck circumference (a well-known OSA biomarker). Receiver operator characteristics curve analysis was used to estimate diagnostic accuracy of neck grasp for predicting OSA. Results Of 201 individuals undergoing PSG, 167 (83%) had the neck grasp test. The remaining 34 could not perform the test because of different factors. Neck grasp was positive in 127 (76%) cases, and 114 (68%) individuals had OSA (apnea-hypopnea index ≥5). Multivariate logistic regression models disclosed a significant association between neck grasp and OSA. The neck circumference was the single covariate remaining independently significant in these models. Neck grasp was not efficient at predicting OSA (sensitivity: 83.3%, specificity: 39.6%, positive predictive value: 0.75 and negative predictive value: 0.53). The area under the curve disclosed only a moderate predictive capability (61.5%) of neck grasp. Conclusion Results do not support the use of neck grasp as an independent predictor of OSA in the study population.